2009
DOI: 10.1162/rest.91.1.20
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Entry on Incumbent Innovation and Productivity

Abstract: Abstract-How does firm entry affect innovation incentives in incumbent firms? Microdata suggest that there is heterogeneity across industries. Specifically, incumbent productivity growth and patenting is positively correlated with lagged greenfield foreign firm entry in technologically advanced industries, but not in laggard industries. In this paper we provide evidence that these correlations arise from a causal effect predicted by Schumpeterian growth theory-the threat of technologically advanced entry spurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
394
3
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 747 publications
(459 citation statements)
references
References 40 publications
(52 reference statements)
15
394
3
8
Order By: Relevance
“…As linking enterprise and social software can be interpreted as a process innovation, the same argument should also hold in this context. Aghion et al (2009) support this argument as they stress the impact of the competitive environment, measured as new firm entry, on the incentives to adopt innovations. However, they show differences for high tech industries and laggards as industries near to the technological frontier react positive in terms of innovative activity to new firm entry, laggards on the other hand are negatively affected.…”
Section: International Activity and Competitive Environmentmentioning
confidence: 91%
See 2 more Smart Citations
“…As linking enterprise and social software can be interpreted as a process innovation, the same argument should also hold in this context. Aghion et al (2009) support this argument as they stress the impact of the competitive environment, measured as new firm entry, on the incentives to adopt innovations. However, they show differences for high tech industries and laggards as industries near to the technological frontier react positive in terms of innovative activity to new firm entry, laggards on the other hand are negatively affected.…”
Section: International Activity and Competitive Environmentmentioning
confidence: 91%
“…As for the first check we estimated the model as a simple probit model without sample selection only with firms using both social software and enterprise software. Table 3 shows the average marginal effects of the probit estimation of equation (2). We use the same exogenous variables as in the bivariate probit with sample selection except for the exclusion restriction.…”
Section: Robustness Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…We discuss our results in light of these different entrant forces. Previous literature, in contrast, largely disregards this aspect and focuses exclusively on the competition effect (e.g., Aghion et al, 2009;Iacovone et al, 2011;Andersson et al, 2012).Fundamental results on the effect of entry on incumbents are scarce. Recent studies found that entrants positively influence incumbents' general innovation activity while incumbents responded asymmetrically, depending on their competitive performance (Aghion and Bessonova, 2006;Aghion et al, 2009;Iacovone et al, 2011;Fritsch and Changoluisa, 2014).…”
mentioning
confidence: 99%
“…Recent studies found that entrants positively influence incumbents' general innovation activity while incumbents responded asymmetrically, depending on their competitive performance (Aghion and Bessonova, 2006;Aghion et al, 2009;Iacovone et al, 2011;Fritsch and Changoluisa, 2014). Such studies utilized quantitative entry measures (e.g., entry rates, import flows, or employment size) and focused on industry-level entry into incumbents' domestic markets.…”
mentioning
confidence: 99%